Sosialisasi Pupuk Organik Untuk Tanaman Hortikultura Menuju Pertanian Berkelanjutan - Sitompul, Hamela Sari; Ainani As’ad, Octasella; Nasution , Nurhadida; Eva Yanti, Mariana; Surbakti, Supriadi; Mulia, Sukri; Yurizki, Yusra (PT. Karya Inovatif Nusantara, 2024)
Socialization of organic fertilizer for horticultural crops aims to provide information regarding the benefits of using organic fertilizer for sustainable agriculture, providing education on making organic fertilizer from agricultural waste. This community service activity was carried out in Central Kuta Village, Karo Regency. Participants in this activity were 35 people from Central Kuta Village, Karo Regency. They work as farmers on horticultural crops such as vegetables and fruit. The methods used were lectures, demonstrations and discussions regarding the benefits of organic fertilizer and how to make organic fertilizer using agricultural waste. The results of service activities show that there is community awareness and interest in processing agricultural waste into organic fertilizer. This is proven by the appreciation and enthusiasm of the community in discussions. People are interested in using their agricultural waste to be processed into organic fertilizer because it can maintain soil fertility or improve soil structure and from an economic perspective it is enough to minimize the budget for purchasing fertilizer.